Penentuan Nilai FICI Kombinasi Ekstrak Etanol Kulit Daun Lidah Buaya (Aloe vera (L) Burm.f) dan Gentamisin Sulfat Terhadap Bakteri Escherichia coli - Lu'lu' A'lana; Rafika Sari; Pratiwi Apridamayanti (Universitas Indonesia, 2017)
The combined use of natural materials and antibiotic compound is one of treatment that can be done against infections caused by bacteria. This combination is expected to inhibit the bacteria is more potent and low side effects. FICI (Fractional Inhibitory Concentration Index) is an index that can indicate the activity of a combination of natural ingredients and antibiotic compounds. FICI would indicate that the combination has a synergistic effect, additive, indifferent or antagonistic. This study aims to determine the FICI to the combination of Aloe vera leavesskin (Aloe vera (L.) Burm.f.)ethanol extractand gentamicin sulphate to the Escherichia coli. Determination of FICI performed with disc diffusion method. The concentration combination of Aloe vera leavesskin (Aloe vera (L.) Burm.f.)ethanol extractand gentamicin sulphate used is 1.25 mg/mL + 2,5 µg/mL did not form a zone of inhibition; and 2.5 mg/ml + 5 µg/ mL forming inhibitory zone of 6.95 mm; 6.75 mm; and 6.65 mm. These results suggest that the combination of Aloe vera leavesskin (Aloe vera (L.) Burm.f.)ethanol extractand gentamicin sulphate against the Escherichia coli has the indifference effect on Escherichia coli, and FICI to this combination is 2.